Prototype System of Processing and Bottled Drink Filling Based on PLC - Claudius Sina Langoda; Theresia Prima Ari Setiyani (SENATIK STT Adisutjipto, 2018)
A prototype system for processing system and filling of drinks packaging using the PLC Omron CPM2A as central to the process and use the HMI as the interface to ease operator to set and view the condition of the system in real-time. There are 3 types of choice of materials that can be processed, in the process of processing liquid material will be transmitted to the main tank to be processed by means of heated and stirred with a mixer. When finished processing the results of processing will be filled into bottles. The results of tests on the prototype in part the processing in accordance with the design. There are 3 choices of beverage products namely coffemilk, Milktea and coffetea. On the third option can be processing operations properly. On the process of charging operations properly. On Charging there is 2 options i.e 200 ml and 250 ml. but for correctness of filling volume experiencing error 7-8%.